Analysis of Residual Stresses in Curved Cutouts of Steel Box Girder Transverse Diaphragms - Rongyong Wang; Yongming Xiong; Hao Ni; Yan Liu; Zhuoyi Chen (Advances in Civil Engineering, 2024)
In order to analyze the characteristics of cutting residual stress distribution at the arc-shaped cutout of steel box girder diaphragm and to study its fatigue cracking mechanism. Taking Xia Zhang Bridge as the engineering background, this paper proposes a systematic method for calculating the residual stress field at the arc-shaped cutout of the diaphragm. First, a mathematical model of the cutting heat source was established for predicting the temperature field changes during the cutting process of the diaphragm. Then, a 3D thermoelastic-plastic finite element model was established using Abaqus to parametrically analysis the residual stresses during the fabrication of the transverse spacer. The results show that the cutting heat source creates a “thermal stagnation” effect at the curved notch, which leads to the local metallurgical transformation of the metal surface layer, which is unfavorable to its fatigue performance. The residual stresses are mainly concentrated near the cutting line, and the transverse residual stresses are lower at the free edge of the cutting line, which is easy to crack, and higher in the middle of the arc section of the arc notch. Inside the transverse bulkhead, at 14.5 mm from the free edge of the cut, in addition to the existence of high longitudinal residual tensile stress, its transverse residual tensile stress is also high, with a peak value of 199.3 MPa. Thermal cutting produces high residual tensile stress at the free edge, and the tensile stress cycle formed under the combined effect of wheel load is one of the reasons for the formation of initial fatigue cracks.